2015
DOI: 10.1177/117718011501100303
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Attachment Styles and Resilience Levels among Aboriginal Adolescents in Canada

Abstract: The history of colonization in Canada has a traumatic intergenerational impact on young Aboriginal people's health, which is evidenced by the wide health disparities (Adelson, 2005; Health Council of Canada, 2012). However, extant research shows that, through resilience, many Aboriginal adolescents overcome adverse situations and develop into healthy adults (Andersson & Ledogar, 2008). Knowledge of the ways and extent to which Aboriginal youth seek support to cope with stressful events may be improved by exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This can be a major contributing factor in the translation of intergenerational trauma through the generations, and as such, is critical for renewal (Isobel et al, 2019). Research has emphasized the importance of having a strong family connection or secure attachment with caregivers to strengthen cultural attachment (Krakouer et al, 2018) and resilience (Redman-MacLaren et al, 2017; Sam et al, 2015). Ultimately, poor cultural attachment can potentially lead to the absence of connection to culture, which can be harmful to Aboriginal and Torres Strait Islander people’s identity development and resilience (Renshaw, 2019).…”
Section: Intergenerational Trauma and The Impact On Cultural Connectionmentioning
confidence: 99%
“…This can be a major contributing factor in the translation of intergenerational trauma through the generations, and as such, is critical for renewal (Isobel et al, 2019). Research has emphasized the importance of having a strong family connection or secure attachment with caregivers to strengthen cultural attachment (Krakouer et al, 2018) and resilience (Redman-MacLaren et al, 2017; Sam et al, 2015). Ultimately, poor cultural attachment can potentially lead to the absence of connection to culture, which can be harmful to Aboriginal and Torres Strait Islander people’s identity development and resilience (Renshaw, 2019).…”
Section: Intergenerational Trauma and The Impact On Cultural Connectionmentioning
confidence: 99%
“…Living with diabetes predisposes people to higher risk of psychological conditions like depression and excessive stress, both of which already disproportionately affect those living in poverty (Sam, Ghosh, and Richardson 2015;. Depression has been linked to long-term chronic diseases such as T2DM in studies in other countries (Darvyri et al 2018;Heidari et al 2017).…”
Section: Spirituality Mental Wellness and Chronicitymentioning
confidence: 99%
“…Some studies have indicated that adolescents with low parental attachment security exhibit lower self-esteem, more problem avoidance, more ineffectual anger, and more internalized symptoms (Allen, Moore, Kuperminc, & Bell, 1998). By contrast, adolescents with high attachment security display better emotional adjustment (Engels, Finkenauer, Meeus, & Dekovic, 2001), lower levels of loneliness (Kerns & Stevens, 1996), better self-resilience (Sam, Ghosh, & Richardson, 2015), less drug abuse (Cooper, Shaver, & Collins, 1998), and fewer mental health problems (including depression and behavioral problems; Rawatlal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%